ANKLE1 as New Hotspot Mutation for Breast Cancer in Indian Population and Has a Role in DNA Damage and Repair in Mammalian Cells - Bakshi, Divya; Katoch, Archana; Chakraborty, Souneek; Shah, Ruchi; Sharma, Bhanu; Bhat, Amrita; Verma, Sonali; Bhat, Gh. Rasool; Nagpal, Ashna; Vaishnavi, Samantha; Goswami, Anindya; Kumar, Rakesh (Frontiers in Genetics, 2021)
Breast cancer has replaced cervical cancer as being the most common and having the highest mortality among women in India. ANKLE gene is conserved among organisms during evolutionary succession and is a member of LEM family proteins in lower metazoans and are involved in critical functions in the nuclear architecture, gene expression and cell signaling. ANKLE-1 is the human ortholog of LEM-3 and is involved in DNA damage response and DNA repair. Whole Exome Sequencing (WES) of paired breast cancer samples was performed and ANKLE-1 was found to be a new possible hotspot for predisposition of breast cancer. The mass array genotyping for breast cancer further confirmed the ANKLE-1 association with the studied population of this cancer. To elucidate the role of ANKLE-1 in DNA damage, it was knocked down in MCF-7 breast cancer cell line and the expression of γH2AX was assessed. ANKLE-1 knockdown cells displayed elevated levels of γ-H2AX foci in response to the cisplatin induced replication stress. The localization pattern of ANKLE-1 further emphasized the role of ANKLE-1 in DNA repair process. We observed that ANKLE-1 is required for maintaining genomic stability and plays a role in DNA damage and repair process. These findings provided a molecular basis for the suspected role of ANKLE-1 in human breast cancer and suggested an important role of this gene in controlling breast cancer development among women in India.